Sesquiterpenoids from the Stem Bark of Aglaia simplicifolia and Their Cytotoxic Activity against B16-F10 Melanoma Skin Cancer Cell - Ghina Izdihar; Al Arofatus Naini; Desi Harneti; Rani Maharani; Nurlelasari Nurlelasari; Tri Mayanti; Agus Safari; Kindi Farabi; Unang Supratman; Mohamad Nurul Azmi; Yoshihito Shiono (Indonesian Journal of Chemistry, 2021)
Four sesquiterpenoid derivatives, i.e., 4β,10α-dihydroxyaromadendrane (1), caryophyllenol-II (2), senecrassidiol (3), and clovane-2β,9α-diol (4) have been isolated from the stem bark of Aglaia simplicifolia. The chemical structures of compounds 1-4 were determined based on spectroscopic data, including one and two-dimensional NMR and mass spectroscopy. In addition, these sesquiterpenoids 1-4, were also tested for their cytotoxic activity against B16-F10 melanoma skin cancer cell lines through in vitro assay. Among the isolated compounds 1-4, compound 1 showed the highest activity with an IC50 value of 44.8 μg/mL, suggesting the presence of a cyclopropane ring that plays an essential role in cytotoxic activity against B16-F10 melanoma skin cancer cell lines.